Case report: Morphological changes evident after manual therapy in two cases of late-diagnosed developmental dysplasia of the hip - Fludder, Christian J.; Keil, Braden G.; Neave, Melissa J. (Frontiers in Pediatrics, 2023)
Background Late diagnosed Developmental Dysplasia of the Hip (DDH) is the detection of DDH after 3 months of age and is associated with significantly poorer outcomes than when diagnosed and managed early. Late diagnosed DDH has lower rates of success with bracing, higher rates of surgery and higher rates of complications, including avascular necrosis of the femoral head and early osteoarthritis of the hip. We describe two cases of late-diagnosed DDH which demonstrated changes in femoroacetabular joint morphology on radiographic interpretation after a 6-month trial period of manual therapy. Case Presentation Two cases (13 and 30 months of age) with late-diagnosed DDH presented to a private chiropractic clinic for conservative, non-bracing management. One case had unilateral DDH and the other bilateral DDH. A trial of manual therapy was utilized over a 6-month period. Both cases demonstrated changes to femoroacetabular morphology as well as improvements in gross motor activity and lower extremity muscle tone. Conclusion Manual therapy, as an adjunct or alternative to static bracing, may be of benefit in individuals with late-diagnosed DDH not responding to bracing, and prior to more invasive interventions. Additional cases of manual therapy-based management of this condition are required to inform the design of future trials to investigate this hypothesis.